Afirmasi Positif Guru Dalam Meningkatkan Kecintaan Siswa Terhadap Al-Qur’an Pada Mata Pelajaran Tadabbur Ayat Di SMP Binar Sumenep : Positive Teacher Affirmations in Enhancing Students' Love for the Qur'an in Tadabbur Ayat Subject at Binar Middle School Sumenep - Riyadatul Inayah; Fathorrozy (Educan, 2025)
The low enthusiasm of students in learning the Qur'an, especially in the subject of Tadabbur Ayat, is an important background in this study. The purpose of this study is to describe the form of positive affirmation given by teachers, understand students' perceptions of the affirmation, and identify the obstacles faced by teachers in the process of learning Tadabbur Ayat at SMP Binar Sumenep. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study indicate that positive affirmation in the form of praise, motivation, and spiritual activities such as prayer before studying can increase students' self-confidence, enthusiasm for learning, and love for the Qur'an. Students respond to affirmation with a positive attitude and show an increase in understanding and practicing the contents of the Qur'an. The obstacles faced by teachers such as limited time and diversity of student characters can be overcome with creative and consistent affirmation strategies. The conclusion of this study is that positive affirmation plays an important role in creating a conducive learning atmosphere and strengthening students' emotional relationship with the Qur'an.